2012
DOI: 10.1111/pace.12022
|View full text |Cite
|
Sign up to set email alerts
|

Current Role of Atrioventricular Junction (AVJ) Ablation

Abstract: Atrioventricular junction ablation with permanent pacemaker insertion is a highly effective treatment approach in patients with atrial fibrillation that is resistant to other treatment modalities, especially in the elderly or those with severe comorbidities. This effect likely reflects reversal of rapid ventricular rates and regularizing ventricular rates. There is increasing evidence that cardiac resynchronization therapy devices may be beneficial in selected populations after atrioventricular node ablation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 70 publications
(129 reference statements)
0
13
0
Order By: Relevance
“…It often poses a management challenge, especially in elderly patients with persistent or permanent AF. In those who develop rapid ventricular rates and symptoms refractory to drug therapy, atrioventricular nodal ablation (AVNA) and cardiac pacing is a proven effective therapeutic alternative . However, the strategy is subject to an array of complications including ventricular arrhythmias …”
Section: Introductionmentioning
confidence: 99%
“…It often poses a management challenge, especially in elderly patients with persistent or permanent AF. In those who develop rapid ventricular rates and symptoms refractory to drug therapy, atrioventricular nodal ablation (AVNA) and cardiac pacing is a proven effective therapeutic alternative . However, the strategy is subject to an array of complications including ventricular arrhythmias …”
Section: Introductionmentioning
confidence: 99%
“…Ideally, ablation is performed at the most proximal penetrating part of the His bundle in order to maintain a proximal automatic junctional rhythm and avoid pacemaker dependence. 1 However, since the patient had lost anterograde conduction during AF at the time of the procedure, a His bundle electrogram was imperceptible. After fluoroscopically positioning the ablation catheter where the compact AV node was suspected to be located, extensive mapping in the region failed to identify a His bundle electrogram.…”
Section: Discussionmentioning
confidence: 99%
“…The standard technique of AVJ ablation and device implantation requires two separate vascular access sites with, although infrequent, the potential risk of bleeding, hematoma formation, and arterial puncture with its related complications including arteriovenous fistula or pseudoaneurysm. The incidence of procedure‐related complications has been described to be approximately 3% with the majority being related to vascular access . The timing of AVJ ablation with regard to pacemaker implantation is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…A and B). The catheter was withdrawn with a septal torque until a large His signal was found and then withdrawn further until atrial signals could clearly be identified . The endpoint of ablation was complete atrioventricular (AV) block.…”
Section: Methodsmentioning
confidence: 99%